Validation of a Rapid and Sensitive LC-MS/MS Method for Determination of Exemestane and Its Metabolites, 17β-Hydroxyexemestane and 17β-Hydroxyexemestane-17-O-β-D-Glucuronide: Application to Human Pharmacokinetics Study - Wang, Ling-Zhi; Goh, Sok-Hwei; Wong, Andrea Li-Ann; Thuya, Win-Lwin; Lau, Jie-Ying Amelia; Wan, Seow-Ching; Lee, Soo-Chin; Ho, Paul C.; Goh, Boon-Cher (PLOS ONE, 2015)
A novel, rapid and sensitive liquid chromatography-tandem mass spectrometric (LC-MS/MS) method was developed and validated for the evaluation of exemestane pharmacokinetics and its metabolites, 17β-dihydroexemestane (active metabolite) and 17β-dihydroexemestane-17-O-β-D-glucuronide (inactive metabolite) in human plasma. Their respective D3 isotopes were used as internal standards. Chromatographic separation of analytes was achieved using Thermo Fisher BDS Hypersil C18 analytic HPLC column (100 × 2.1 mm, 5 μm). The mobile phase was delivered at a rate of 0.5 mL/min by gradient elution with 0.1 % aqueous formic acid and acetonitrile. The column effluents were detected by API 4000 triple quadrupole mass spectrometer using electrospray ionisation (ESI) and monitored by multiple reaction monitoring (MRM) in positive mode. Mass transitions 297 > 121 m/z, 300 > 121 m/z, 299 > 135 m/z, 302 > 135 m/z, 475 > 281 m/z, and 478 > 284 m/z were monitored for exemestane, exemestane-d3, 17β-dihydroexemestane, 17β-dihydroexemestane-d3, 17β-dihydroexemestane-17-O-β-D-glucuronide, and 17β-dihydroexemestane-17-O-β-D-glucuronide-d3 respectively. The assay demonstrated linear ranges of 0.4 – 40.0 ng/mL, for exemestane; and 0.2 – 15.0 ng/mL, for 17β-dihydroexemestane and 17β-dihydroexemestane-17-O-β-D-glucuronide, with coefficient of determination (r2) of > 0.998. The precision (coefficient of variation) were ≤10.7%, 7.7% and 9.5% and the accuracies ranged from 88.8 to 103.1% for exemestane, 98.5 to 106.1% for 17β-dihydroexemestane and 92.0 to 103.2% for 17β-dihydroexemestane-17-O-β-D-glucuronide. The method was successfully applied to a pharmacokinetics/dynamics study in breast cancer patients receiving exemestane 25mg daily orally. For a representative patient, 20.7% of exemestane in plasma was converted into 17β-dihydroexemestane and 29.0% of 17β-dihydroexemestane was inactivated as 17β-dihydroexemestane-17-O-β-D-glucuronide 24 hours after ingestion of exemestane, suggesting that altered 17-dihydroexemestane glucuronidation may play an important role in determining effect of exemestane against breast cancer cells.